2016
DOI: 10.1016/j.nicl.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Increased frontal sleep slow wave activity in adolescents with major depression

Abstract: Sleep slow wave activity (SWA), the major electrophysiological characteristic of deep sleep, mirrors both cortical restructuring and functioning. The incidence of Major Depressive Disorder (MDD) substantially rises during the vulnerable developmental phase of adolescence, where essential cortical restructuring is taking place. The goal of this study was to assess characteristics of SWA topography in adolescents with MDD, in order to assess abnormalities in both cortical restructuring and functioning on a local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…However, the between-group differences in positive behavioural consolidation in the early sleep condition are modest [p = .156], and does not provide an adequate explanation for the observed differences in neutral memory consolidation. Interestingly, it has recently been shown that slow-wave activity over the prefrontal cortex during the first NREM sleep episode is greater in depressed adolescents than matched controls (Tesler et al, 2016). The authors of this study speculate that the increase of frontal slow-wave activity in MDD may reflect an altered pruning of synapses in this area, which results in a failure to reduce irrelevant connections.…”
Section: Accepted Manuscriptmentioning
confidence: 61%
“…However, the between-group differences in positive behavioural consolidation in the early sleep condition are modest [p = .156], and does not provide an adequate explanation for the observed differences in neutral memory consolidation. Interestingly, it has recently been shown that slow-wave activity over the prefrontal cortex during the first NREM sleep episode is greater in depressed adolescents than matched controls (Tesler et al, 2016). The authors of this study speculate that the increase of frontal slow-wave activity in MDD may reflect an altered pruning of synapses in this area, which results in a failure to reduce irrelevant connections.…”
Section: Accepted Manuscriptmentioning
confidence: 61%
“…In the only study using a homogeneous sample in terms of age, gender and medication use, a lower delta amplitude and power has been shown in depressed adolescent girls as compared to healthy girls [37]. Recently, it has also been shown that the topographical pattern of SWA distribution in depressed adolescents is characterized by increased SWA over the frontal cortex compared to healthy controls [38]. However, currently there are no studies that measure SWA abnormalities using a homogeneous sample of depressed boys.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, differences in sleep EEG power between patient populations and healthy controls are almost always over a circumscribed brain region and may be a result of the neural circuitry implicated in a specific disorder. For example, in children with attention deficit hyperactivity disorder, an increase in SWA in central regions is observed 41 , while in adolescents with major depressive disorder an increase of SWA over frontal regions is observed 48 . These studies imply that the topography of the sleep EEG may be an additional marker of functional brain circuitry.…”
Section: Introductionmentioning
confidence: 99%